SpectroCube: a European 6U nanosatellite spectroscopy platform for astrobiology and astrochemistry. (May 2020) - Elsaesser, Andreas; Merenda, Fabrice; Lindner, Robert; Walker, Roger; Buehler, Steeve; Boer, Gerben; Villa, Andrés; Hallak, Yanina; Aguado, Fernando; Alberti, Edoardo; Wood, Brian
Abstract: SpectroCube is a CubeSat-based miniaturized in-situ space exposure platform for astrochemistry and astrobiology research. Within a 6 unit (6U, with 1U corresponding to 10 cm x 10 cm x 10 cm) nanosatellite structure, an infrared spectrometer is interfaced with a sample handling system to measure photochemical changes of organic molecules, representing important biomarkers for the detection of life in our solar system and beyond. Monitoring degradation profiles and photochemical reaction kinetics of such biomarkers allows to identify suitable search targets for current and future planetary exploration and life-detection missions. SpectroCube is designed to be launched into a highly elliptical orbit around Earth and therefore allows to expose samples to higher solar UV and energetic particle radiation levels than previous exposure platforms in low Earth orbit, as for example on the International Space Station. In-situ data will be telemetered back to Earth and compared with solar and planetary simulation experiments in ground-based laboratory. We here present the design of SpectroCube, the scientific payload and its subsystems. We demonstrate that with the miniaturisation potential of infrared spectroscopy it is possible to fit the entire optical setup plus a sample handling system for up to 60 individually contained and hermetically sealed samples within less than half of the volume of a 6U CubeSat structure. Therefore, the remaining volume can be entirely used for additional subsystems such as attitude control, propulsion, fuel, onboard computer and telemetry. The design of the scientific payload is based on a commercial off-the-shelf miniaturised Fourier-transform spectrometer consisting of an infrared light source, an interferometer and infrared detector units. The mechanical robustness and suitability of such a system for space applications was assessed. Shock and vibration testing of the mechanically most sensitive unit, the interferometer, was performed and revealed that with adequate damping the spectroscopic performance can be maintained. Additional measurements of test samples conducted with the selected commercial off-the-shelf spectrometer candidate showed that the spectroscopic range, resolution and sensitivity is capable to monitor in situ the photochemical kinetics of important classes of organic molecules and biomarkers for astrobiology and astrochemistry research.